bahasa inggris - Eka Roza Wijaya; Yulia Yasman; Dachriyanus Dachriyanus (Universitas Harapan Bangsa Purwokerto, 2021)
Nurses often face to situations that can cause job stress Nurses often face to situations that can cause job stress. This study aims to determine the factors related to nurse’s job stress at hospitals type B Batam in 2015. The study used descriptive analytic design with cross sectional approach. The sample consisted of 193 nurses by simple random sampling. The results showed more than half of the nurses experienced severe job stress (57%) were derived from heavy workload (64.4%), cases of death and dying (68.4%), emotional preparation inadequate (64.1%), uncertainty about treatment (71.8%), conflicts with doctors (73.9%), problems with co-workers (70.7%), problems with the supervisor (70.8) and problems with patient and family (66.7%). There is significant relathionship of eight of job stress factors to nurse’s job stress (p<0,05). The most dominant factor affected nurse’s job stress is a problem with a co-worker. The study recommends that we need to improve communication among in nurses